Leaching Behavior of Pb, Cd, and Cu from Domestic Solid Waste Over Three Types of Soil Columns Under Different Rainfall Loading - Haddad, Marwan; Al-Nuri, Qusai (Journal of Environmental Science and Engineering Technology, 2024)
Long-term raining over accumulated solid waste disposal dumps would result in heavy metal contamination in both soil and groundwater, specially when no separation of industrial waste is made in Nablus Area of Palestine. A column leaching experiments were conducted to study the leaching behavior of Pb, Cd, and Cu from domestic solid waste over three types of local soils, clay, sandy, and a mix of both in one, three and five 100 cm depth, soil packed in eleven plastic columns under different rainfall loading of one, five, and ten years of average annual rainfall. Experimental results showed that (1) The concentration of heavy metals in leachate passing through soil were highest out of sandy soil followed by sandy clay soil and the least was out of clay soil, (2) As the applied layer of solid waste over the soil in the columns increases, the concentration of heavy metals and organic matter increase, (3) As the amount of rainwater applied over solid waste increases, the concentration of heavy metals decreases in the leachate from all columns, (4) The concentration of heavy metals absorbed by clay soil was much higher than than those in the sandy and mixed clay-sandy soil indicating that clay soil is good for metal remediation or removal but not suitable for using the soil for agricultural production purposes, and (5) The TOC removal efficiencies were greater in clay and clay-sandy soil and significantly improve with time.